Riqueza arbórea útil de la Sierra de Manantlán, México: el árbol no es solo madera - Pineda-López, Ma. del Rosario; Benz, Bruce; Santana-Michel, J.; Rosales-Adame, J.; Cevallos-Espinoza, J.; Muñoz-Mendoza, Ma. Elizabeth (CATIE, Turrialba (Costa Rica), 2020)
6 páginas, 3 ilustraciones, una figura, 16 referencias.